The Influence Of CEO Narcissism On Corporate Social Responsibility Disclosure - Kadek Ernawan; Debby Ratna Daniel (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2019)
This study examined the influence of CEO narcissism on the corporate social responsibility disclosure. The research sample used in the study is mining companies listed on the Indonesia Stock Exchange for the 2015-2018 periods, with a total of 30 companies. Quantitative methods with multiple linear regression data analysis techniques were used in this study. The results of this study supported the research hypothesis that CEO narcissism has positive effects on the corporate social responsibility disclosure. CEO's tenure at the company, CEO ownership of company shares, debt to asset ratio and company size also affect the corporate social responsibility disclosure. The results of the study are consistent with the upper echelon theory that the organization is a reflection of its top management and the characteristics of top management influence the results of the organization. The results of this study contribute to the upper echelon research and corporate social responsibility disclosure.